KOMUNIKASI ANTARPRIBADI DALAM TOXIC RELATIONSHIP PACARAN PADA MAHASISWA UNIVERSITAS NEGERI GORONTALO - Sumarjo; Tamu, Yowan; Elvita Hussa, Deby Astuty (Jambura Jurnal Ilmu Komunikasi, 2023)
In romantic relationships, things don't always go smoothly. There are many reasons why aconsensual relationship between people of different genders becomes an unhealthy relationship.For example, the lack of openness between partners is one of the causes of problems in romanticrelationships. An unhealthy relationship can have a negative impact on the physical and mentalhealth of someone involved in the relationship. The condition of an unhealthy romanticrelationship is called a toxic relationship.This research aims to find out how interpersonal communication processes and social exchangesoccur in toxic relationships among Gorontalo State University students. The research methodused is a qualitative descriptive approach using social penetration theory and Social ExchangeTheory as analytical tools.The research results show that the relationship level that leads to a toxic relationship occurs inthe communication context, namely verbal and nonverbal communication. The findings of verbalcommunication that occurred in the relationships of several informant couples were that thecouple received harsh words, lies, insults towards the partner, demeaned and intimidated thepartner. Meanwhile, findings related to nonverbal communication that occurred were thatseveral informants often received physical violence such as punches and even throwing thingswhen a conflict occurred. Second, the social exchange that occurs in relationships, namely costsand rewards. The costs received in a relationship include momentary emotional satisfaction andsufficient financial needs. Apart from that, the rewards that occur include frequently feelingstressed, anxious, and losing freedom in relationships.